A CASE STUDY ON GENDER NEUTRAL LAWS AND CONSTITUTION - Yadav, Rinki (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Gender-neutral laws aim to eliminate biases in legal systems and establish a framework of equality, irrespective of gender. This study explores the integration and impact of gender-neutral legislation on constitutional frameworks globally, with a focus on India. It examines the role of constitutional mandates, judicial interpretations, and legislative efforts in advancing gender neutrality. Through a comparative analysis, the study evaluates best practices from other countries, highlighting the challenges and prospects of adopting gender-neutral laws in diverse socio-legal environments. The findings emphasize the importance of inclusive legal reforms in achieving a fair and equitable society.